2014
DOI: 10.1007/s11999-014-3853-x
|View full text |Cite
|
Sign up to set email alerts
|

Does Patient Sex Affect the Anatomic Relationships Between the Sternoclavicular Joint and Posterior Vascular Structures?

Abstract: Background Despite increased concern for injury during surgical reconstruction of the sternoclavicular joint, to our knowledge there are few studies detailing the vascular relationships adjacent to the joint. Questions/purposes We investigated sex differences in the following relationships for sternoclavicular joint reconstruction: (1) safe distance from the posterior surface of the medial clavicle's medial and lateral segments to the major vessels, (2) length of the first costal cartilage and safe distance fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…9,15 While uncommon, injuries to the SC joint can be severe because of the proximity to posterior vascular structures. 15,16 The risk of injuries to these and other nearby structures is higher with posterior dislocations 13,15 when compared with anterior dislocations. However, anterior dislocations are more common because of the greater strength of the posterior capsule, 13,24 with 1 biomechanical study finding 50% stronger force required to cause a posterior dislocation.…”
mentioning
confidence: 99%
“…9,15 While uncommon, injuries to the SC joint can be severe because of the proximity to posterior vascular structures. 15,16 The risk of injuries to these and other nearby structures is higher with posterior dislocations 13,15 when compared with anterior dislocations. However, anterior dislocations are more common because of the greater strength of the posterior capsule, 13,24 with 1 biomechanical study finding 50% stronger force required to cause a posterior dislocation.…”
mentioning
confidence: 99%
“…There are few articles that compare distances such as age, sex, and BMI. Merriman et al 14 found differences between the sexes, with a smaller distance from the medial clavicle to the BCV in females. Regarding these variables, our data demonstrate that the left SCJ is closer to the hilar structures than to the right side; in women both SCJ are closer to the BCV, esophagus and pulmonary apices compared to men; patients with BMI <25 have lower distances up to the BCV and esophagus.…”
Section: Discussionmentioning
confidence: 96%
“…Despite the importance of these factors and the increasing prevalence of MRI, investigations into MR imaging of the clavicle and the SCJ remain limited. Nevertheless, some associations have been made, revealing correlations between clavicular parameters, sex, and age, primarily through CT scans and cadaver examinations of removed and prepared clavicles [ 12 , 30 ]. Existing literature also explores the measured asymmetry of the right and left clavicles in cadavers via direct measurement from removed, washed, and boiled clavicles as well as from radiographs [ 12 , 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%